Wear evaluation method of drilling shaft sinking hob based on rock slag morphology and rock abrasiveness - Hua CHENG; Bao XIE; Zhishu YAO; Chuanxin RONG; Jian LIN (Meitan xuebao)
Aiming at the serious wear problem of hob in deep and large vertical shaft constructed by drilling method in Jurassic strata in western China, a method for evaluating the wear of hob in drilling method is put forward, taking the drilling method of sinking shaft in a coal mine in the west as the research object. Firstly, based on field investigation, the wear degree and wear distribution characteristics of hob in different strata are analyzed, and relevant quantitative indexes are put forward. Secondly, the rock slag of shaft drilling rig is pretreated on site, and the image recognition method is used for post-processing, and the geometric morphology of rock slag is statistically analyzed, and its cumulative distribution law is described by exponential distribution function. Then, taking Pearson coefficient as the correlation evaluation index, the influence of rock slag particle distribution and mineral composition on hob wear index is explored, and the causes of easy wear of drilling shaft sinking hob in western China are expounded. Finally, based on the correlation analysis method, several main influencing parameters are selected, and the prediction formula of hob wear index for different rock strata is developed by using nonlinear fitting tools, and the evaluation method of replacing hob on site is put forward. The results show that: the wear of drilling hob is closely related to the geological conditions of rock strata, and the number of hob consumed per unit footage in different strata is in the order of argillaceous cemented muddy stratum > calcareous cemented mud, sand interbedded stratum ≈ calcareous and iron cemented sandy stratum > extremely weak cemented sandy stratum; The deep grinding area of shaft sinking cutterhead in western drilling method is easy to concentrate on B, C and D cutter rings, while the center cutter and its vicinity are mostly shallow grinding areas; The statistical characteristics of geometric morphology of rock slag can indirectly reflect the wear degree of hob in different strata; The particle size distribution of sand and mudstone strata in western China conforms to exponential function, and the correlation coefficient R2 is 0.976−0.997. The uniformity coefficient of slag obtained according to the fitting function has the highest correlation with the wear uniformity index. The reasons for the increase of hob wear in muddy strata and mud-sand interbedded strata can be attributed to mud and sand of rock slag; Taking the box width, the proportion of large particles, the uniformity coefficient and the rock abrasiveness index of the roundness distribution of rock slag as the main characterization parameters, a hob wear prediction model suitable for different strata is obtained. Compared with the field measurement, the prediction success rate of the model is 90.9%; The proposed evaluation method of hob wear can provide a useful reference for the decision-making of lifting and changing tools on the spot.